Teknik Inkuiri Upaya Peningkatan Kemampuan Membaca Pemahaman Siswa SMP Plus Darussalam Blokagung Banyuwangi - Ali Manshur (IAI Darussalam, 2016)
This research is a classroom action research with inquiry techniques whose main purpose is for students to find the main idea and the main sentence of the paragraph. This classroom action research is conducted approximately one month ie mid-May to mid-June. The subjects of this study are students of SMP Plus Darussalam which totaled 34 students and female sex. Analysis of data used based on each stage of research that has been done. The results of the classroom action research process that has been implemented are known that the ability of students in learning to read the understanding of techniques has increased from the implementation of the cycle 1 to cycle 2. This can be seen from the percentage of students' ability to read comprehension find the main idea and the main sentence. From the research results can be concluded that the implementation of classroom action research with inquiry techniques can improve the ability to read comprehension in finding the main idea and the main sentence